Lacrimal gland lymphoma: Role of radiation therapy - Natasha Townsend; Aruna Turaka; Mitchell R Smith (Oman Journal of Ophthalmology, 2012)
Background: To report the clinical and treatment outcome of patients with lacrimal gland lymphoma (LGL) treated with radiation therapy (RT) at Fox Chase Cancer Center, Philadelphia, PA, USA. Materials and Methods: Institutional review board approved retrospective chart review of eight patients and literature review. Results: The study patients included six males and two females with a mean age of 70 years (range 58-88 years). The mean follow-up period was 23 months (range 3-74 months). Four patients had mucosa-associated lymphoid tissue (50%) lymphoma and four patients had other non-Hodgkin′s lymphoma variants. Four patients had bilateral disease (50%). Four patients had primary LGL (stages I-IIAE, 50%) and four had LGL as part of systemic lymphoma (stage IVAE, 50%). The median RT dose was 2987 cGy (range 2880-3015 cGy). All patients had complete response to RT with symptomatic relief. Minimal dry eye was seen in all patients. There were no late effects such as corneal ulcer, radiation retinopathy, maculopathy, papillopathy, or secondary neovascular glaucoma. Conclusions: RT alone is an extremely effective treatment in the curative management of localized LGL and provides durable, local control of secondary LGL.